Chloride penetration resistance of fine recycled aggregate concrete - Amadi I. G.; Beushausen H.; Alexander M.G.; Surana S. (MATEC Web of Conferences, 2022)
This study investigates the chloride penetration resistance of fine recycled aggregate concrete (FRAC). Six concrete mixes comprising 0.45 and 0.55 w/b were prepared using fine recycled aggregates (FRA) at 0, 25 and 50% by volume replacement of natural sand. The chloride penetration resistance of the concrete was tested using the surface electrical resistivity (SER), chloride conductivity index (CCI), and the bulk diffusion tests. The SER and CCI tests were conducted after 28 days and 180 days of wet curing, while the bulk diffusion test was carried out after 28 days of wet curing and 180 days of exposure to chloride solution. Results show that the SER of FRA concrete was comparable to the control concrete, at all ages tested. The 28-day CCI of the concrete was impacted as FRA replacement levels increased, whereas at 180 days of testing, the FRA concrete mixes showed more significant improvement in CCI than the control natural aggregate concrete (NAC). The bulk diffusion results indicate that, for each w/b, the chloride diffusion profiles of the control and FRA concrete are comparable.